Profitability of tomato (Solanum lycopersicum) cultivation in Nuh district of Haryana - KUMAR, RAJ; SAIN, VEER; SUMIT, SUMIT; KUMAR, PAWAN; KUMAR, AJAY (The Indian Journal of Agricultural Sciences, 2021)
The present study was carried out during 2017-18 on the basis of of highest production of tomato (Solanum lycopersicum L.) in Nuh district of Haryana. The study was carried out to examine the cost and returns, marketing cost, margins, price spread and marketing efficiency of tomato through different channels. A sample of 30 tomato growers was taken purposively from various villages in Tauru block of Nuh District of Haryana. There was regular variation in price of tomato due to its semi-perishable nature and immediate postharvest sales by the cultivators. The study revealed that direct marketing of tomato was found to be most profitable in Channel-IV, i.e. Producerconsumer among all other prevalent marketing channels due to the non-existence of intermediaries between producer and ultimate consumer. Study concluded that the estimated total costs, gross returns, net returns, and B: C ratios of tomato cultivation were `183474, 289248, 105774 and 1.58 per ha, respectively.